Komunikasi Krisis Dalam Pemerintahan Provinsi Banten - Mansur Mansur; Ani Febriani; John Chaidir (Amal Insani Foundation, 2023)
In 2020, the world experienced the Corona Virus Disease (COVID-19) pandemic. Our country is no exception; Indonesia was not spared from the confirmed virus outbreak from China. The Corona Virus Disease (COVID-19) outbreak in Banten Province has shaken all aspects of human life, not only in the health sector but also in the economic, social, cultural, and political fields. Changes in all aspects of life have brought us into a new era; that is to say, we have entered conditions to make peace with the Coronavirus pandemic for almost 3 (three) years. In 2023, President Joko Widodo on June 21, 2023, officially announced the revocation of the COVID-19 pandemic status in Indonesia. With this repeal, Indonesia will enter an endemic period. During the Covid-19 pandemic, the Provincial Government of Banten remained responsive in providing public services related to health, the economy, and others for the community. Even during this pandemic, the economy of Banten Province experienced a slowdown. For this reason, the Provincial Government is trying to schedule a New Normal policy so that the economic impact due to the pandemic does not cause a prolonged crisis. This policy relates to regional development planning (RPJMD). The Provincial Government of Banten needs to re-examine its mid-term plan considering that all programs are shifting focus to handling Covid-19. The government has three alternatives in medium-term planning: stick with the original plan, make moderate revisions, or replace it with a new plan based on updated assumptions with the arrival of the Covid-19 pandemic and the economic impact. The Provincial Government of Banten continues to coordinate and communicate well with the Central Government and Regency/City Governments throughout Banten.